Cover Picture: Scalable Synthesis of Palladium Icosahedra in Plug Reactors for the Production of Oxygen Reduction Reaction Catalysts (ChemCatChem 9/2016). Issue 9 (9th May 2016) - Wang, Helan; Niu, Guangda; Zhou, Ming; Wang, Xue; Park, Jinho; Bao, Shixiong; Chi, Miaofang; Cai, Zaisheng; Xia, Younan
Abstract : The Front Cover shows a polymer tube containing a continuous flow of plug reactors used for the synthesis of colloidal metal nanocrystals. In their Full Paper, Wang et al. report how such plug reactors can be applied to the continuous and scalable production of palladium icosahedral nanocrystals with uniform and controllable sizes. More information can be found in the Full Paper by Wang et al. onpage 1658 in Issue 9, 2016 (DOI:10.1002/cctc.201600060 ).